2008
DOI: 10.7202/016935ar
|View full text |Cite
|
Sign up to set email alerts
|

De l’incertitude de la naissance au risque obstetrical : les enjeux d’une définition

Abstract: La réforme de la périnatalité française, mise en place à la fin des années 1990, repose sur une catégorisation du risque obstétrical (bas, moyen, haut). Selon le niveau de risque estimé, la femme enceinte doit être adressée à une maternité de niveau I, II ou III. À partir d’une enquête effectuée par des observations et des entretiens auprès d’obstétriciens et de sages-femmes, il s’agit, dans cet article, de montrer que la définition de ces catégories du risque est en elle-même un enjeu. En effet, leur contesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…In addition, childbirth in France is governed by high technologization. This technological management of childbirth falls under the culture of ‘obstetric risk’ described above, which is strong in France ( Carricaburu, 2005 , Carricaburu, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, childbirth in France is governed by high technologization. This technological management of childbirth falls under the culture of ‘obstetric risk’ described above, which is strong in France ( Carricaburu, 2005 , Carricaburu, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found these phenomena to be classified by clinicians as innately risky, located along a continuum going from low to high risk (Coxon, Scamell, & Alaszewski, 2012;. As a consequence, this 'lens of risk' (Heyman, 2013;Heyman, Alaszewski, Shaw, & Titterton, 2009) tends to reduce the number of pregnancies and deliveries regarded as 'normal' (Scamell, 2016), or renders births only 'normal' in retrospect (Carricaburu, 2007). Midwives and physicians tend to interpret discrete signs or variations as problematic, which we argue 'casts the future principally in negative, potentially catastrophic terms' (Alaszewski & Burgess, 2007, p. 349).…”
Section: Risk In Childbirth In High-income Countriesmentioning
confidence: 99%
“…While uncertainty, fear, and the unknown have always been part of the birthing experience, these feelings are currently being rationalised through the category of risk (Carricaburu, 2007;Carricaburu, Castra, & Cohen, 2010). This epidemiological category is also instrumental in organising pregnancy care provision in developing countries like Brazil.…”
Section: Contextmentioning
confidence: 99%